The impact of jury experience on perception of the criminal prosecution system - Pyo, Jimin (International journal of law, crime and justice, 2018)
The present study tested the impact of jury experience on citizens' perceptions of the criminal prosecution system. Based on deliberative democratic theory which predicts the beneficial impact of jury experience on citizen-jurors' confidence and knowledge in law and the justice system, it was hypothesized that jury experience would be associated with favorable impression of the criminal prosecution system and that jury experience would have a positive impact on citizens' perceived knowledge of the criminal prosecution system. The present study through analyzing data collected by the American Prosecutors Research Institute (APRI), examined the effect of jury experience (versus no jury experience) on perceptions of the criminal prosecution system. Results show that jury experience positively influences citizen-jurors' impression and perceived knowledge of the criminal prosecution, supporting an attitudinal and educational impact of jury experience. Potential limitations of the study and policy implications are discussed.